Synthesis of 4-hydroxy-1-methyl-4-(2-furyl)-3-(2- furylhydroxymethyl) piperidine and Transformation into perhydro[1,3,2]dioxaborinino[5,4-c]pyridine - Phuong, Nguyen Thi Thanh; Van, Tran Thi Thanh; Tuan Anh, Le; Hieu, Truong Hong; Van, Tran Thach; Nhung, Dao Thi; Thimophievich, Soldatenkov Anatoly (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 3, 2017)
Having been synthesized successfully heterocyclic system, namely 2-aryl-N-methyl-4,8a-di(α-furyl)perhydro[1,2,3]dioxaborinino-[5,4-c]pyridine contains two piperidine and dioxaborinine rings. This new heterocyclic system was prepared from the reaction of N-methyl-3-(α-hydroxyfuryl)-4-(α-furyl)-γ-piperidol and some derivatives of arylboronic acid. The structure of new substances was confirmed by physical-chemical method including 1 Н NMR, IR, MS. Futhermore, PASS online Program investigated that di(α-furyl)perhydro[1,2,3]dioxaborinino-[5,4-c]pyridine derivatives have high potential of bioactivities such as dermatology, spasmology, anticoagulant and antipsoriatic agent … which promote us to develop the new method affording this kind of compounds.